Additive Therapy for Advanced Stages of Glaucoma - I. R. Gazizova; V. E. Korelina; E. P. Goncharuk (Oftalʹmologiâ, 2023)
Purpose of the study: to evaluate the efficacy and feasibility of using brimonidine 0.2 % in the additive therapy of patients with advanced stages of glaucoma. Materials and methods. There were 59 patients (77 eyes) with advanced stages of primary open-angle, glaucoma (POAG) aged 68 to 83 years in the study. Patients were randomized into 2 groups depending on the received antihypertensive therapy. The first group (I) included 32 people (41 eyes) who used a fixed combination of a prostaglandin analogue (APG) or a carbonic anhydrase inhibitor (CAI) with a beta-blocker (BB) for the treatment of POAG. The second group (II) consisted of 27 patients (36 eyes) who had the α2-adrenergic agonist brimonidine — S3 added to the previously available combination of APG or ICA with BB. The observation period was 6 months. Results. Application of brimonidine — SZ in the additive therapy of advanced stages of glaucoma led to an additional hypotensive effect. By the end of the observation period in the group of patients treated with brimonidine, intraocular pressure decreased by an additional 10 % from the initial level. A good hypotensive effect contributed to an increase in functional parameters. Analysis of the results of static automatic perimetry showed a positive trend in the mean deviation (MD) and standard deviation pattern (PSD), which may indicate a neuroprotective effect of the drug. All patients noted good tolerability of treatment. Throughout the observation period, patients maintained a high level of adherence and performance.